Interactions of black carrot concentrate powder as a natural coloring agent with gelatine and sucrose in model gummy samples - Ilyas, Atalar (2025)
With growing consumer concerns about the sustainability and safety of synthetic food colorings, the food industry is increasingly turning to natural colorants derived from plants. Anthocyanins from black carrots are preferred as natural food colorants in the food industry. However, the product composition in which the colorants are used affects the pigments' color properties and stability behaviors. This study aims to determine the interaction between black carrot juice concentrate powder (BCCP) with gelatine and sucrose for model gummy samples and to develop models for the optimal composition of the product. Hardness (9.90–21.77 N), resilience (0.61–0.82), cohesiveness (0.95–0.98), springiness (0.27.5–0.63 mm), gumminess (9.63–21.30 N), and chewiness (3.15–13.36 Nxmm) properties of model gummy samples were determined by texture profile analysis. TPC values for gummy candy samples ranged from 6.87 to 44.3 mg GAE/kg, while inhibition values for AAC were 0.00%–13.4%. BCCP x gelatin and BCCP × sucrose interactions were determined to be significant for texture parameters such as hardness, gumminess, chewiness, and L∗, a∗, b∗, and chroma values (P < 0.05). The optimal composition for samples was determined as 32.03 g/100 g sucrose, 21 g/100 g gelatin solution, and 0.27 g/100 g BCCP, respectively, by considering changes in hardness, springiness, hardness variation and ΔE∗ values at the end of accelerated shelf-life (ASL) conditions. Incorporating polyphenol-containing BCCP affects gummies' colour stability and texture.